Quantitative risk assessment of salmonellosis through pork consumption in Vietnam - Sinh Dang-Xuan (Rakuno Gakuen University, 2018)
Food safety is an important public health concern worldwide, especially in emerging economies, including Vietnam, where pork production plays an important role in both livelihood and diet. Throughout studies conducted in this PhD thesis, the overall goals of this research was to assess the extent of Salmonella contamination along the smallholder pork value chain in Vietnam and determine the risk of salmonellosis in humans to aid in the production of the risk reduction strategies. We have used both participatory and field epidemiological approaches to explore food safety perceptions and practices among a variety of different occupational streams involved in the smallholder value chain and pork consumers, and to identify Salmonella prevalence and potential risk factors along the chain. A consumer survey and laboratory experiments were also conducted to determine pork handling practices and cross-contamination risks of Salmonella in pork in Vietnamese households. We have developed a quantitative microbial risk assessment (QMRA) model to quantify salmonellosis risks in the household through pork consumption. The first study findings relating to food safety practices and perceptions held by pork value chain associated employees and consumers indicated that most slaughterhouse workers acquired knowledge and experience of food safety through ‘‘learning by doing’’ rather than from training. The workers and sellers often use the same cloths to dry the meat and clean equipment without thinking of contamination risks. They were found to possess some accurate perceptions about swine and foodborne diseases but had misperceptions of zoonoses risks. Consumers perceived that pork freshness was a strong indicator of food safety and perceived that sellers may have health issues that they are trying to conceal by wearing protective equipment (e.g., gloves, masks). Veterinary and public health staff emphasized the gap between regulations and food safety practices. The investigation results on Salmonella contamination and risk factors demonstrated Salmonella prevalence to be 36.1% (26/72), 38.9% (58/149), and 44.7% (97/217) on pig pen floors, pig carcasses in slaughterhouses and cut pork in pork shops, respectively. The risk factors for Salmonella prevalence on pig pen floors included having a pig pen next to the household (p = 0.055) and free access to the farm by visitors (p = 0.061). Slaughter areas close to lairage without hygienic measures was a risk factor for carcass contamination at the slaughterhouse (p = 0.031). For pork shops, presence of flies or insects on the pork at shop (p = 0.021) and use of cloths at pork shop (p = 0.023) were risk factors. The Salmonella prevalence on pig carcasses and cut pork was significantly lower in winter compared to other seasons. A household survey revealed that most people (71%) used the same knife and cutting board for both raw and cooked pork. Simulation experiments indicated that hands, washwater, knives and cutting boards exposed to raw contaminated pork were the main source of Salmonella spread to cooked pork. 78% of cooked pork samples were contaminated with Salmonella when the same hands, knife and cutting board were used for both raw and cooked pork. Using the same cutting board resulted in 67% of cooked pork samples becoming contaminated with Salmonella. The results on quantifying salmonellosis using a QMRA model found the annual incidence rate of salmonellosis in humans to be estimated as 17.7% (90% CI: 0.89 - 45.96). Parameters with the greatest influence risk were household pork handling practices followed by prevalence of Salmonella in pork sold in the central market. Our results highlighted the need for prioritization of education and training among pork value chain associated employees on food safety risks and proper handling. Risk factors for Salmonella contamination at farms, slaughterhouses and markets need to be addressed by planning effective and affordable control options for human salmonellosis by improving pork hygiene along the informal pork value chain. Control measures may include improving the safety of retail pork and improving household hygiene. Moreover, findings also provided information relating to the level of understanding about cross-contamination in households. From these insights, future education programs may be based on communication with households about strategies for improved food safety. Our work constitutes original evidence in food safety with the aim of understanding pork safety and its heath impact. From this research, intervention strategies to improve food safety with links to food safety risk assessments, management and communication may be put into place.